Field investigations of multidrug-resistant Salmonella Infantis epidemic strain incursions into broiler flocks in England and Wales. Issue 6 (1st November 2020) - Newton, Kate; Gosling, Becky; Rabie, André; Davies, Rob
ABSTRACT: Salmonella Infantis is a major public health concern and has become established in the broiler sector in some European countries, as well as globally, and is frequently multidrug resistant (MDR). Three broiler farms in England and Wales, which had incursions of MDR S. Infantis between 2013 and 2017, were investigated longitudinally. The company feed mill and two associated hatcheries were intensively sampled. Following each visit, advice on cleaning, disinfection and other control measures for Salmonella was given to help eliminate S. Infantis from the premises . Four samples collected from inside the broiler houses after cleaning and disinfection were Salmonella -positive, indicating cleaning and disinfection within houses was generally effective. However, the exterior of persistently infected houses remained substantially contaminated and feeding systems could not be sampled. Clearance of S. Infantis from affected houses requires additional attention to decontamination of these aspects. Sixty S. Infantis isolates were tested for antimicrobial susceptibility by disk diffusion tests. All isolates were MDR, with resistance to at least nalidixic acid (Na), tetracycline (T), compound sulphonamide (Su), streptomycin (S) and furazolidone. This is a similar resistance pattern to the previously identified MDR (NaSSuT) clone in some European countries. The study shows that to remove S . Infantis from premises effectively, a combined approach to poultry houses and the surrounding farm environment is necessary. A revised cleaning and disinfection programme was developed that was associated with the clearance of MDR S. Infantis from persistently infected and newly infected broiler flocks, and UK livestock remains free of MDR S. Infantis. RESEARCH HIGHLIGHTS Standard cleaning and disinfection protocols did not completely eliminate infection. A revised cleaning and disinfection programme was developed. Disinfecting feeder lines and external areas was key to eliminating S. Infantis. Identified similar antimicrobial resistance pattern to MDR epidemic S. Infantis.